1995
DOI: 10.1007/bf00185390
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine neoplasms of the larynx importance of the correct diagnosis and differences between atypical carcinoid tumors and small-cell neuroendocrine carcinoma

Abstract: Findings in the present study have confirmed that the diagnosis of neuroendocrine tumors of the larynx (NETL) requires that a panel of neuroendocrine markers and electron microscopy be performed. This means that the clinician must be aware of the clinical presentations of such patients and should send fresh biopsy specimens to the clinical laboratory for optimal tissue studies. As shown in this study, the possibility of misdiagnosis of an atypical carcinoid tumor (ACT) is rather high. In establishing a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…2,7 Accurate cytologic identification of these rare neoplasms in exfoliative cytologic material can be difficult or impossible. Immunocytochemistry could be helpful in such cases.…”
Section: Malamou-mitsi Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…2,7 Accurate cytologic identification of these rare neoplasms in exfoliative cytologic material can be difficult or impossible. Immunocytochemistry could be helpful in such cases.…”
Section: Malamou-mitsi Et Almentioning
confidence: 99%
“…2,3,7,8,14,[17][18][19][20]22 One should keep in mind that repair or pseudocarcinomatous epithelial atypia, especially in intensively inflamed benign lesions or due to underlying neoplasia, can result in false positive cytologic diagnoses.…”
Section: Malamou-mitsi Et Almentioning
confidence: 99%
“…In contrast to small cell lung cancer, only 8% of this tumor of the larynx metastasize to the central nervous system and then only as a preterminal event [33]. Many patients (about half) have cervical metastases on initial presentation [4] and the tumor should be considered as a disseminated disease at presentation [11]. In a review by Gnepp et al [32], 73% of patients with laryngeal small cell neuroendocrine carcinoma died of disease with widespread metastases, with a mean survival time of 9.8 months (range 1-26 months).…”
mentioning
confidence: 99%
“…Descriptions of treatments are rare. 6,36,40,4,56,58,59 In 1989, Ferlito and Friedmann proposed that painful skin/subcutaneous metastases should be treated surgically. 44 van der Laan et al (2012) suggested that salvage surgery, including palliative metastasectomy, had an important role in the treatment of laryngeal NEC.…”
Section: Discussionmentioning
confidence: 99%
“…It was thus suggested that chemotherapy was ineffective. Gripp et al (1995) 58 used somatostatin to treat skin metastases from atypical laryngeal carcinoids. However, the drug was no better than other chemotherapies.…”
Section: Discussionmentioning
confidence: 99%